Interactive methods of teaching Turkish as a foreign language (Journal of Oriental Studies, 2018)
This article is about learning Turkish language as a foreign languageeffectively through interactive methods. Including in it, there are free andeasy ways to teach the Turkish language through the role play and businessgames. Also described knowledge of games and their types.